ANALISIS BUTIR SOAL EVALUASI PEMBELAJARAN PAI MENGGUNAKAN PROGRAM ANATES - Elviana Elviana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The purpose of this study is to determine the characteristics of PAI Learning Evaluation items using ANA Test program. This research uses a quantitative descriptive approach and documentation technique in data collection. The document was in form of final semester exam questions which were 25 items of multiple choice test. The number of documents were 26 similar to the number of students who responded to the problem. Data analysis used ANA Test version 4 program. The results showed that the power difference was low, only 20% items could distinguish between upper and lower groups, the level of difficulty was moderate, there were 64%, the test validity was 0.24 in low category, only 24% was significant, the reliability was low and the effectiveness of the distractor was only 32 % functioning properly.